Proteasome inhibition as a potential therapeutic target in thymic cancer - Okada, Satoru; Benter, Louisa; Schrell, Leon; Müller, Denise; Selcen, Selen; Bohnenberger, Hanibal; Schneider, Carolin; Schneider, Günter; Lohrberg, Melanie; Koch, Raphael; Overbeck, Tobias R.; von Hammerstein-Equord, Alexander; et al. (Cell death & disease, 2025)
Multimodal radio-chemotherapy is the mainstay of treatment for unresectable thymoma (TH) and thymic carcinoma (TC), but there is an urgent need for other therapeutic strategies in these rare tumors. The epithelial cells of the normal thymus express the three major proteasome classes: constitutive, immunoproteasome, and thymoproteasome, making thymic epithelial tumors potential candidates for treatment with proteasome inhibitors. In a drug screen of 120 cytotoxic agents, the two thymic carcinoma cell lines 1889c and MP57 showed exquisite sensitivity to the proteasome inhibitor carfilzomib (PR-171). Immunohistochemistry, gene expression, and in vitro functional studies were used in a comprehensive sample collection to investigate the correlation between immunoproteasome subunit expression and response to carfilzomib. 50% of TC and a substantial proportion of TH strongly expressed immunoproteasome subunits and showed functional activity of β1i (PSMB9), β2i (PSMB10), and β5i (PSMB8). INF-γ treatment induced immunoproteasome expression and increased cell sensitivity to carfilzomib, while siRNA knockdown reduced carfilzomib response in vitro. Carfilzomib synergized with BCL2 family protein inhibitors (navitoclax or AZD5991), suggesting that drug combinations could be used to reduce the dose of each drug to minimize toxicity. Notably, thymic carcinomas differed from squamous cell carcinomas in other organs by higher levels of β5i (PSMB8) and constitutive proteasome β5 (PSMB5). We hypothesize that TC (and probably many TH) are uniquely suited for treatment with proteasome inhibitors alone or in combination with selective BH3 mimetics.
Online veröffentlicht: 04. Dezember 2025
Gesehen am 11.02.2026